The social imaginary in the digital world. Notes on two investigations about New Technologies & Internet - Chavarro, Luis (2019)
Starting from the consideration of the imaginary and the key conceptions so that concepts such as social significance, institution and functions are put into effect, as indicated by Castoriadis, this article highlights the work of Daniel H. Cabrera to understand the imaginary of new technologies, as well as Patrick Flichy’s work on the imaginary of the Internet, based on Ricoeur’s notions of ideology and utopia. Both the new digital technologies and the Internet are the ideal complement characteristic of what is usually called the information society from the point of view of the technological determinism. The examination of these two works of the imaginary in times of globalization through technology is a defense of critical thinking that allows us to understand why in this new century democracy seems to go back to the nineteenth century forms since it has become premise to think of a life without the requirement of the State, submerged in a connected individualism and virtual public opinion that seems to be still far from what the public agora meant for Greek democracy.